A Strategic Roadmap for Maximizing Big Data Return - Abdel-Fattah, Manal A.; Helmy, Yehia; Mohamed Hassan, Thanaa (International Journal of Integrated Engineering, 2019)
Big Data has turned out to be one of the popular expressions in IT the last couple of years. In the current digital period, according to the huge improvement occurring in the web and online world innovations, we are facing a gigantic volume of information. The size of data has expanded significantly with the appearance of today's innovation in numerous segments, for example, assembling, business, and science. Types of information have been changed from structured data-driven databases to data including documents, images, audio, video, and social media contents referred to as unstructured data or Big Data. Consequently, most of the organizations try to invest in the big data technology aiming to get value from their investment. However, the organizations face a challenge to determine their requirements and then the technology that suits their businesses. Different technologies are provided by variety of vendors, each of them can be used, and there is no methodology helping them for choosing and making a right decision. Therefore, the objective of this paper is to construct a roadmap for helping the organizations determine their needs and selecting a suitable technology and applying this conducted proposed roadmap practically on two companies.